Early physical activity promotes lower prevalence of chronic diseases in adulthood - Fernandes, Romulo A. [UNESP]; Zanesco, Angelina [UNESP] (Nature Publishing Group, 2010)
Epidemiological studies have shown high rates of occurrence of arterial hypertension and type 2 diabetes mellitus among adults, and early preventive actions are extremely relevant for public policy strategies. The purpose of this study was to analyze the relationship between the prevalence of arterial hypertension and type 2 diabetes in adulthood and physical activity (currently and in childhood/adolescence). A retrospective study was carried out from March to November of 2009. Data were collected through interviews, and both diseases were assessed through self-report and confirmed by previous medical diagnosis. Current physical activity and that performed in childhood (7-10 years old) and adolescence (11-17 years old) were analyzed. of the 1436 adults analyzed in this survey, similar to 61% were women (n=881). Respondents' ages ranged from 18 to 94.8 years, and 20.2% of the total participants were >= 65 years old. Our results show that men (18%) were more physically active than women (9.4%), whereas younger respondents and those with more formal education exhibited greater physical activity levels (P<0.001). Obese subjects presented lower physical activity levels (P=0.027). Physical activity in youth was associated with lower rates of occurrence of arterial hypertension (odds ratio (OR) 0.42 (95% confidence interval (CI) 0.29-0.62)) and type 2 diabetes mellitus (OR=0.29 (95% CI=0.15-0.56)) in adulthood, but current physical activity was not related to these outcomes. Our study reveals a positive relationship between early physical activity in both childhood and adolescence and lower rates of occurrence of endocrine and cardiovascular diseases in adulthood. Hypertension Research (2010) 33, 926-931; doi: 10.1038/hr.2010.106; published online 24 June 2010
Keywords: adolescents; children; diabetes; physical activity